2011
DOI: 10.1007/s12664-011-0109-5
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association of primary iron overload and common HFE gene mutations with liver cirrhosis in adult Indian population

Abstract: The frequency of PIL, and the HFE gene mutaion (C282Y) are both rare in Indian patients and explain why hemochromatosis is a rare cause of liver cirrhosis in India. A highly significant H63D allele frequency in HBV and alcohol-related cirrhosis suggest a possible predisposing role for liver fibrosis of this allele.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…In our study we tried to demonstrate that the epidemiology of the HH and HFE gene mutation in Iran is completely different from that found in the West, and also to emphasize the infrequency of the C282Y mutation in Iran [2]. In recent publications from countries such as India, similar results were found and all the data were in favor of a minor contributory role of HH in the development of cirrhosis in these countries which is different from in the West [3]. Finally I want to emphasize the effect that the presence of the HFE gene mutation has on the fibrogenesis of other liver diseases such as alcoholic or viral hepatitis [4] and this should be investigated in future studies in Iran.…”
mentioning
confidence: 68%
“…In our study we tried to demonstrate that the epidemiology of the HH and HFE gene mutation in Iran is completely different from that found in the West, and also to emphasize the infrequency of the C282Y mutation in Iran [2]. In recent publications from countries such as India, similar results were found and all the data were in favor of a minor contributory role of HH in the development of cirrhosis in these countries which is different from in the West [3]. Finally I want to emphasize the effect that the presence of the HFE gene mutation has on the fibrogenesis of other liver diseases such as alcoholic or viral hepatitis [4] and this should be investigated in future studies in Iran.…”
mentioning
confidence: 68%
“…In our study, the least iron content in the liver was found in the patients with biliary cirrhosis, which has also been reported by Batts ( 8 ). It seems that stainable iron in biliary cirrhosis is rare and, if present, the amount of stainable iron is low ( 17 , 18 ). In none of our Prussian-blue slides of biliary cirrhosis was the whole tissue loaded with iron.…”
Section: Discussionmentioning
confidence: 99%
“…The mutations though not studied in CVI, are thought to be rare in the Indian population. [5][6][7][8][9][10][11][12][13][14] This may explain the absence of accumulation and excretion of haemosiderin-alternative disease causation is thus postulated as a mechanism of disease.…”
Section: Discussionmentioning
confidence: 99%